The relative severity of patients receiving short-duration withdrawal management services in the hospital and community setting: A retrospective cohort study from Ontario, Canada - Campitelli, Michael; Babujee, Amreen; Sharpe, Isobel; Huang, Anjie; Wong, Fiona; Kurdyak, Paul (International Journal of Population Data Science, 2026)
Diverting patients visiting the emergency department for withdrawal management towards services in the community, rather than an inpatient bed, could provide more supportive care while reducing strain on the hospital system. Our objective was to compare the severity of patients receiving short-duration withdrawal management in the hospital and community settings to help inform this newly developed care pathway. We conducted a retrospective cohort study in Ontario, Canada by linking a community-based addictions program dataset to the health administrative databases housed at ICES. Unique patients receiving short-duration withdrawal management (0-4 days) in the hospital and community settings between January-December 2021 were identified; short-duration cases were of interest as these are likely presentations that are manageable in the community. Negative binomial regression models were used to compare hospital admission rates in the past year (a proxy for severity) between those receiving withdrawal management in the hospital versus community setting. We included 3,342 and 2,499 patients receiving short-duration withdrawal management in the hospital and community settings, respectively. After adjusting for demographics, the rate of all-cause (Relative Rate [RR]=3.29, 95% Confidence Interval [95%CI] 2.94-3.69), mental health and addictions-related (RR=3.17, 95%CI 2.72-3.70), and substance use-related (RR=5.38, 95%CI 4.49-6.43) admissions in the past year were significantly higher for those receiving withdrawal care in the hospital setting compared with the community setting. A care pathway designed to redirect short-duration cases of withdrawal from the hospital to community setting would need to ensure community-based treatment centres were adequately resourced to manage patients of greater severity.